2022
DOI: 10.3389/fbioe.2022.836764
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Reactive Oxygen Species in Bone Regeneration: A Glance at Potential Therapeutics and Bioengineering Applications

Abstract: Although the complex mechanism by which skeletal tissue heals has been well described, the role of reactive oxygen species (ROS) in skeletal tissue regeneration is less understood. It has been widely recognized that a high level of ROS is cytotoxic and inhibits normal cellular processes. However, with more recent discoveries, it is evident that ROS also play an important, positive role in skeletal tissue repair, specifically fracture healing. Thus, dampening ROS levels can potentially inhibit normal healing. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 170 publications
(221 reference statements)
0
18
0
1
Order By: Relevance
“…In vitro studies in human and mouse cells have shown that ROS is an important activator for various cell signaling pathways, mediated MSCs differentiation and cell fate ( Yang et al, 2013 ; Atashi et al, 2015 ). Accumulating evidence suggesting the alteration of the redox state causes systemic changes that can coordinate osteoblast differentiation or osteoclast activity that relat to the bone remodeling process in human and animal models ( Domazetovic et al, 2017 ; Schreurs et al, 2020 ; Sheppard et al, 2022 ). The supplementation of trace minerals can alleviate the negative effect of oxidative stress and optimize the bone quality in human and broilers ( Santos et al, 2020 ; Savaram Venkata et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies in human and mouse cells have shown that ROS is an important activator for various cell signaling pathways, mediated MSCs differentiation and cell fate ( Yang et al, 2013 ; Atashi et al, 2015 ). Accumulating evidence suggesting the alteration of the redox state causes systemic changes that can coordinate osteoblast differentiation or osteoclast activity that relat to the bone remodeling process in human and animal models ( Domazetovic et al, 2017 ; Schreurs et al, 2020 ; Sheppard et al, 2022 ). The supplementation of trace minerals can alleviate the negative effect of oxidative stress and optimize the bone quality in human and broilers ( Santos et al, 2020 ; Savaram Venkata et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…H 2 O 2 is well-known ROS signaling intermediate in response to tissue injury ( Sanchez-de-Diego et al, 2019 ). ROS activates signaling that influences vital pathways, such as Wnt or TGF/BMP pathways, which are response to fracture healing and tissue repairment mechanism by regulating osteogenic differentiation of stem cells ( Wang et al, 2017 ; Sheppard et al, 2022 ). MSCs can migrate to the sites of injury in response to various stimuli, including cytokines or growth factors, and differentiate into tissue-specific cell types to repair the damaged region ( Merimi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bone health and homeostasis are the result of a delicate balance between the activity of osteoblasts and osteoclasts. When maxillofacial bone suffers bone defect in response to periodontitis, trauma or tumor, cells such as osteocytes, osteoblasts and osteoclasts will are exposed to oxidative stress ( Sheppard et al, 2022 ). However, ROS may impede or undermine the complicated bone regeneration process through a variety of signaling pathways.…”
Section: Interaction Between Implant Materials Factors and Reactive O...mentioning
confidence: 99%